Geneza kryzysu bankowego w Argentynie w latach 2001-2002 - Ostalecka, Agnieszka (The Genesis of the Banking Crisis in Argentina Between 2001 and 2002, 2006)
The article presents the review of causes of the banking crisis outbreak in Argentina, which took place in between 2001 and 2002. As a starting point, the article discusses the macroeconomic and banking system situation before the crisis. The next step is to carry out a review of the publications concerning Argentinean crisis in order to identify the main factors, which increase the probability of the Argentinean crisis outbreak. As a result 5 main causes are separated with simultaneous pointing out their influence of Argentinean banking crisis outbreak.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (4); 2006; nr 1119, s. 215-226